1997
DOI: 10.1016/s0735-1097(96)00522-0
|View full text |Cite
|
Sign up to set email alerts
|

Infarct Size Limitation by a New Na-H Exchange Inhibitor, Hoe 642: Difference From Preconditioning in the Role of Protein Kinase C

Abstract: Hoe 642 enhanced myocardial tolerance against infarction, and this enhanced tolerance was not influenced by anesthetic agents commonly used for infarct size studies. Infarct size limitation by Hoe 642 was not inhibited by polyB, suggesting that cardioprotection by Na(+)-H+ exchange inhibition is not PKC mediated and thus may be unrelated to preconditioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
2

Year Published

1998
1998
2009
2009

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(52 citation statements)
references
References 41 publications
2
48
0
2
Order By: Relevance
“…This could be achieved by inhibiting I NHE or late I Na . Both approaches were cardioprotective in experimental models of ischemia/ reperfusion, since in this situation, an excessive increase of [Na + ] i contributes to progressive cytosolic and mitochondrial Ca 2+ -overload and thus, the induction of apoptosis through activation of the mitochondrial PTP [78,135,168,189]. Also in animal models of heart failure, both the inhibition of I NHE by cariporide and of late I Na by ranolazine reduced [Na + ] i and improved EC coupling and LV remodeling [6,34,38,62,163,202].…”
Section: Discussionmentioning
confidence: 99%
“…This could be achieved by inhibiting I NHE or late I Na . Both approaches were cardioprotective in experimental models of ischemia/ reperfusion, since in this situation, an excessive increase of [Na + ] i contributes to progressive cytosolic and mitochondrial Ca 2+ -overload and thus, the induction of apoptosis through activation of the mitochondrial PTP [78,135,168,189]. Also in animal models of heart failure, both the inhibition of I NHE by cariporide and of late I Na by ranolazine reduced [Na + ] i and improved EC coupling and LV remodeling [6,34,38,62,163,202].…”
Section: Discussionmentioning
confidence: 99%
“…In animal studies it exerted a powerful anti-infarct effect when present during an ischemic insult, but showed no benefit when present only after reperfusion. 39 In the EXPEDITION trial, 40 cariporide was tested in patients undergoing coronary bypass surgery. It was started prior to surgery and infusion continued for 24 h. Unfortunately, mortality caused by cerebrovascular events increased in the treatment group.…”
Section: Circulation Journal Vol73 July 2009mentioning
confidence: 99%
“…The amino acid sequence of NHE-1 has been demonstrated to be highly homologous in humans, rats and rabbits (495%, NoeÈ l & Pouysse gur, 1995), and for this reason T-162559 is thought to be capable of inhibiting rabbit NHE-1 and conferring on the rabbit heart tolerance against ischaemia and reperfusion. Cariporide and other NHE-1 inhibitors exert a similar cardioprotective eect in rabbits (Hendrikx et al, 1994;Miura et al, 1997;Munch-Ellingsen et al, 1998). In the rabbit model, T-162559 did not show a dose dependency between the two doses.…”
Section: Discussionmentioning
confidence: 84%
“…It protects the heart against ischaemia and reperfusion injury, limiting myocardial infarct size and suppressing ventricular ®brillation (Scholz et al, 1995;Aye et al, 1997;Miura et al, 1997). In addition, it has been reported that bolus intravenous administration of cariporide reduced the incidence of cardiac death and recurrent myocardial infraction in coronary artery bypass graft patients, based on the results of the GUARDIAN trial (The roux et al, 2000).…”
Section: Introductionmentioning
confidence: 99%